Novel antibody–drug conjugates for triple negative breast cancer. (May 2020) - Nagayama, Aiko; Vidula, Neelima; Ellisen, Leif; Bardia, Aditya
Triple negative breast cancer (TNBC) is a heterogenous subtype of breast cancer often associated with an aggressive phenotype and poor prognosis. Antibody–drug conjugate (ADC), comprising of a monoclonal antibody linked to a cytotoxic payload by a linker, is gaining increasing traction as an anti-cancer therapeutic. Emerging ADC drugs such as sacituzumab govitecan (IMMU-132) and trastuzumab deruxtecan (DS-8201a) are in late stages of clinical development for patients with metastatic breast cancer, including TNBC. In this article, we review and discuss the development and clinical application of ADCs in patients with advanced TNBC.